Life cycle assessment comparison of emerging and traditional Titanium dioxide manufacturing processes. (15th February 2015) - Middlemas, Scott; Fang, Z. Zak; Fan, Peng
Abstract: Titanium dioxide (TiO2 ) is used as pigment in a wide variety of domestic and industrial applications, and is becoming an increasingly valuable nanomaterial. TiO2 is manufactured by the traditional sulfate process or high temperature chloride process. Several hydrometallurgical processes for manufacturing TiO2 have recently emerged to reduce the environmental impact of TiO2 production. A new process is reported that features alkaline roasting of titania slag (ARTS), with subsequent washing, leaching, solvent extraction, hydrolysis, and calcination stages, and implements the recycling and regeneration of alkaline and acid process streams to minimize waste generation. A virtual ARTS processing plant is described in detail and is used to conduct an LCA comparison with the sulfate, chloride, and Altairnano processes. The cumulative energy demand (CED) and total CO2 emissions for the ARTS process are 92.6 MJ/kg TiO2 and 7.47 kg CO2 /kg TiO2, respectively, which compares favorably with the traditional and Altairnano processes. Graphical abstract: CED contribution from coal, natural gas, oil, nuclear, renewable, and unspecified energy sources for traditional and emerging TiO2 manufacturing processes using slag, ilmenite, synthetic rutile and titaniferrous magnetite feed stocks. Data sources indicated with symbols. (+):Grubb and Bakshi, 2010 ; (*):Liao et al., 2012 ; (○):Reck and Richards, 1999 . Highlights: LCA of emerging and traditional TiO2 making processes reviewed. New hydrometallurgical process for making TiO2 pigment described in detail. Cumulative energy demand and CO2 emissions of different processes compared. New process shows potential for reductions in energy consumption and CO2 emissions.